1990
DOI: 10.1038/347768a0
|View full text |Cite
|
Sign up to set email alerts
|

Localization of nitric oxide synthase indicating a neural role for nitric oxide

Abstract: Nitric oxide (NO), apparently identical to endothelium-derived relaxing factor in blood vessels, is also formed by cytotoxic macrophages, in adrenal gland and in brain tissue, where it mediates the stimulation by glutamate of cyclic GMP formation in the cerebellum. Stimulation of intestinal or anococcygeal nerves liberates NO, and the resultant muscle relaxation is blocked by arginine derivatives that inhibit NO synthesis. It is, however, unclear whether in brain or intestine, NO released following nerve stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
1,122
4
49

Year Published

1992
1992
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,856 publications
(1,221 citation statements)
references
References 26 publications
46
1,122
4
49
Order By: Relevance
“…Physiological levels of nitric oxide are necessary for the survival of differentiated cerebellar granule cells (Ciani etĀ al ., 2002). nNOS is highly expressed in cerebellar granule neurons (Bredt etĀ al ., 1990; Bredt & Snyder, 1992). We previously reported that āˆ’/āˆ’ mice show erectile dysfunction and decreased hypothalamic cGMP level (Lu etĀ al ., 2008; Han etĀ al ., 2013), both could result from negation of nitric oxide by mitochondrial superoxide.…”
Section: Resultsmentioning
confidence: 99%
“…Physiological levels of nitric oxide are necessary for the survival of differentiated cerebellar granule cells (Ciani etĀ al ., 2002). nNOS is highly expressed in cerebellar granule neurons (Bredt etĀ al ., 1990; Bredt & Snyder, 1992). We previously reported that āˆ’/āˆ’ mice show erectile dysfunction and decreased hypothalamic cGMP level (Lu etĀ al ., 2008; Han etĀ al ., 2013), both could result from negation of nitric oxide by mitochondrial superoxide.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggest that endo thelium-derived factors are not involved as damage of the endothelium in vitro or in vivo was found not to influence the central vasodilator response to CO2 (Gotoh et al, 1987;Toda et al, 1989). However, the pioneering work of Bredt et al (1990) has demon strated NO synthase immunoreactivity in neurons and also in perivascular nerves contacting smooth muscles (but not in the smooth muscle cells). An astrocyte-derived vasorelaxing factor with similar properties to those of NO has also been described (Murphy et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…5,42 Many functions may be produced by combinations of both types of neurotransmission. In the piano playing example presented above, in addition to the relevant synaptic mechanisms, the Ā®nger movements can be more precise in the presence of adequate preparation including changes in brain tone (probably mediated by noradrenaline), and the visual perception of the tennis game may require neuronal receptivity to be set at a high level, probably involving several neurotransmitters, including nitric oxide 50 and dopamine 51 in the retina, serotonin and histamine in the lateral geniculate nucleus 52,53 and noradrenaline in the visual cortex. 54 These e ects appear to be primarily non-synaptically mediated.…”
Section: Nonsynaptic DI Usion Neurotransmissionmentioning
confidence: 99%